A NEW SPECIES OF CASSINE (CELASTRACEAE) FROM INDIA - N. Sasidharan; K. Swarupanandan (Research Center for Biology, 1992)
The new species Cassine kedarnathii Sasi. & Swarup. is described from the Silent Valley National Park (India) and illustrated.